Peran Auditor dan Teknologi dalam Mencegah Kasus Fraud - Nurul Qalbi Insaniah; Nurmi; Wahyuni (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
Financial integrity and organizational image are often threatened by fraudulent actions such as embezzlement and financial statement manipulation, which can undermine public trust and employee morale. Therefore, preventive measures and fraud detection must be a top priority. Auditors play a crucial role in healthy corporate governance by relying on their independence and professional competence to detect internal control weaknesses and assess fraud risks. This study employs a descriptive qualitative approach to analyze the role of auditors and technology in fraud prevention. The findings indicate that e-Audit, AI-based technology, and big data analytics positively influence fraud detection, while information technology and blockchain enhance audit performance. However, the success of fraud prevention still depends on the auditor's ability to understand accounting and auditing standards, as well as analytical skills. The synergy between auditor capabilities and appropriate technology can significantly improve internal control systems and fraud detection..